2013
DOI: 10.3928/01477447-20130122-32
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis Caused by Pantoea agglomerans in a Closed Fracture in a Child

Abstract: Development of osteomyelitis in a closed fracture is rare. Although it has been reported that trivial trauma may be associated with the subsequent development of acute osteomyelitis, no evidence has been found that fractures are involved in the etiology of osteomyelitis. Only 25 cases (11 in adolescents) of osteomyelitis after closed fracture have been reported in literature. The authors report a case of osteomyelitis in an 8-year-old girl after a forearm fracture involving the diaphysis of the radius and ulna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…When we reviewed the literature, there was one synovitis, seven osteomyelitis, one periostitis, and six septic arthritis cases caused by P. agglomerans described between 1978 and 2019 (►Table 1). [4][5][6][7][8][9][10][11][12] Thirteen of 15 patients were boys (88%) and median age was 7.4 years. In most cases, diagnosis was delayed 4 to 6 weeks after trauma because of the low virulence of the bacterium and late recognition of the foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…When we reviewed the literature, there was one synovitis, seven osteomyelitis, one periostitis, and six septic arthritis cases caused by P. agglomerans described between 1978 and 2019 (►Table 1). [4][5][6][7][8][9][10][11][12] Thirteen of 15 patients were boys (88%) and median age was 7.4 years. In most cases, diagnosis was delayed 4 to 6 weeks after trauma because of the low virulence of the bacterium and late recognition of the foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…In the words of researchers, “some species are plant pathogens while some are found in humans, especially Pantoea agglomerans . [ 6 ] It is noteworthy that, on the one hand, P. agglomerans is a well-documented human pathogen,[ 4 7 8 9 ] even reported to be a confirmed contaminant, isolated from consumed powdered infant formula milk in neonatal ICU ward, a first report from Iran,[ 10 ] while on the other hand, it is being used for the production of “Andrimid,” a newer, promising acetyl-CoA carboxylase inhibitor, a potent, broad-spectrum antibiotic! [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…The genus is frequently isolated from plant surfaces, seeds, soil, and water [53] and includes many species infective for humans. As reported by Delétoile et al [54], P. agglomerans , which is widely distributed in nature occupying, as preferential habitats, water, soil, and plants, is an opportunistic pathogen that causes numerous cases of infections to soft tissues and bones [55,56,57,58]. Marais et al [59] also reported on a rare case of cervical spondylodiscitis caused by P. agglomerans .…”
Section: Discussionmentioning
confidence: 99%